Care and Empathy as a Crucial Quality for Social Change - Rupčić Kelam, Darija; Kelam, Ivica (Conatus - Journal of Philosophy, 2022)
Suppose the contemporary man of the 21st century puts under control one of the most significant issues of humankind, like the shortage of food or hunger, epidemics of contagious diseases, and wars. Then remains the question which man first encountered at the dawn of the third millennium; it is a question of what to do with yourself. This question becomes extremely important if we consider biotechnology and information technology’s immense growing power. What to do with so much power? Nevertheless, the most obvious question is whether a man has become better and more moral, empathetic and caring than he was. What seems to concern contemporary man includes happiness, divinity, and ultimately his improvement as a moral agent and his immortality. We will try to answer these and many other questions through the paradigm of ethics of care, closely related to the question of empathy. The paper will discuss and highlight empathy and care as crucial means for social change. Therefore, the main aim of such ethics is to alleviate human suffering and anxiety and promote human well-being and happiness. Can care, compassion, and empathy ethics provide us with some answers and become a path to a more moral world?